The digital classroom as a site of political intervention? Existential-phenomenological considerations in the entangled times of digitalization and authoritarianism - Rautenberg, Niclas (Frontiers in Communication, 2025)
The digitalization of the university coincides with a strengthening of totalitarian projects in liberal democracies. For their own sake as well as for democracy’s, academics must be able to intervene in moments when the classroom becomes a site of anti-democratic resentment. But what happens when the classroom becomes increasingly digitalized, i.e., when seminars and lectures take place via digital media instead of the ‘physical’ classroom or lecture hall? This article presents a philosophical, more specifically: existential-phenomenological, argument to cast doubt on the adequacy of such online spaces to battle anti-democratic resentment. In order to show this, it discusses three key phenomenological critiques of digital learning—e.g., Dreyfus’s critique of telelearning, Wellner’s ‘Zoom-bie’ student, and Aagaard’s ‘habitual distraction’. Pace Dreyfus and Wellner, I argue that the problem with the digital learning situation is not one of fundamental lack, but of overabundance. Building on Aagaard, I understand the screen as a portal that solicits several projects simultaneously, whereby the instructor attempting to political intervene rivals for attention with myriad other sources ‘luring in’ the habitually attuned student. The concluding section of the paper makes some general observations about the private nature of digital learning environments and of the platforms that they rival for attention with, and the need to think political resistance in online spaces anew.